Analysis of the Kanamycin in Raw Milk Using the Suspension Array. (3rd September 2012) - Wang, Yanfei; Zou, Mingqiang; Han, Yi; Zhang, Fan; Li, Jinfeng; Zhu, Xiaoyan
Abstract : With the monoclonal antibody against kanamycin being prepared successfully, a bead-based indirect competitive fluorescent immunoassay was developed to detect kanamycin in milk. The fact that there was no significant cross-reaction with other aminoglycoside antibiotics implied that the monoclonal antibody was highly specific for kanamycin. The limit of detection (LOD) and the 50% inhibition concentration (IC50 ) in raw milk were 3.2 ng/mL and 52.5 ng/mL, respectively. Using the method developed in this study, the kanamycin concentrations were monitored in raw milk after the intramuscular administration of kanamycin in sick cows. Compared to the conventional enzyme-linked immunosorbent assay (ELISA), the method using the suspension array system was more sensitive. The results obtained in the present study showed a good correlation with that of the ELISA.